fabrication and study the characteristic of PbTelSi (Baghdad Science Journal, 2005)
In this research has been the manufacture and study the properties of the solar cell type retail hybrid manner thermal evaporation emptiness were studying the properties of the cell at room temperature showed measurements stream circuit behavior linear cell manufacturers reached were calculated efficiency tool cell manufacturers, as well as the expense of workers filling the cell